Teacher Education, supervised practicum, and the body: Biopower and social exclusion (Research, Society and Development, 2025)
The study aims to investigate how Physical Education students, from the 5th to the 8th semester of the Bachelor’s program at an institution located in the interior of the State of Rio de Janeiro, experience constraints that call into question their technical competence, as a result of the ideal body standards promoted by the media. Data were collected through an online questionnaire and semi-structured interviews. Students’ narratives suggest that normative discourses—shaped largely by capitalism and amplified by the media—affect their self-image and perceived technical ability, illustrating how biopower regulates conduct and contributes to the exclusion of individuals who do not fit the hegemonic body model. The findings indicate that Physical Education curricula should broaden the debate on corporeality to value subjectivity, dismantle reductionist perceptions, and acknowledge the social and cultural dimensions that constitute the body.